Orthotic Device Use in Canine Patients: Owner Perception of Quality of Life for Owners and Patients - Lee, Sera; Wendland, Theresa M.; Rao, Sangeeta; Magee, Christianne (Frontiers in Veterinary Science, 2021)
Orthotic devices are an established treatment for neuromusculoskeletal disease in the human population. Orthoses are an emerging veterinary therapy due to limited practitioner experience, availability of devices, and published data from veterinary patient outcomes. Expanding client education and veterinary expertise in the application of orthoses may allow greater access and successful utilization of these devices to treat appendicular disease. While orthoses have the potential to improve quality of life for veterinary patients, consideration needs to be made for owner related factors with device use. Owner satisfaction and experience may greatly impact compliance with treatment recommendations; therefore, it is crucial that owner expectations are met. The purpose of the present study was to evaluate owner-reported outcomes of orthoses for canine patients and owners’ subjective responses to their experiences utilizing a promoter score. It was hypothesized that owners’ impressions of their pets’ experience with the device would influence reported quality of life of both owner and pet, and would also impact owner likelihood to recommend a veterinary orthosis to a friend. An anonymous online survey was sent to 136 clients of a single veterinary orthosis manufacturer. Fifty-six surveys were completed and included for analysis. The owner’s reported quality of life was in agreement (P = 0.02) with reported pet quality of life. There was also a higher likelihood (P = 0.02) for the owner to recommend a veterinary orthotic device to a friend when perceived pet quality of life was positive as compared to negative or neutral. Willingness to recommend an experience to a friend is a reflection of satisfaction with the experience. The dependence of owner and pet quality of life should therefore guide therapeutic decisions for patient management and client communication to ensure that the orthosis experience is positive for both patient and owner.